1996
DOI: 10.1152/jappl.1996.80.1.298
|View full text |Cite
|
Sign up to set email alerts
|

Splenic contraction, catecholamine release, and blood volume redistribution during diving in the Weddell seal

Abstract: The spleen of the Weddell seal (Leptonychotes weddelli) may contract and inject red blood cells (RBCs) into the peripheral circulation during diving, but evidence for this hypothesis is indirect. Accordingly, we measured splenic dimensions by ultrasonography, plasma catecholamine concentrations, hemoglobin concentration, and hematocrit in five Weddell seals before and after intravenous epinephrine during halothane anesthesia and while awake at the surface after voluntary dives. Spleen size was reduced immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
96
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 19 publications
3
96
0
Order By: Relevance
“…Qvist et al (2) recorded a distinct rise in Weddell seal Hct during diving and suggested that the total red cell mass is partitioned between general circulation and the splenic reservoir. The concept of splenic red cell storage is well accepted by many researchers, and a diving-induced sympathetic vasoconstriction is thought to be the stimulus for splenic contraction and subsequent injection of oxygenated RBCs into circulation (2,4,6,7). Strong evidence supports this line of reasoning.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Qvist et al (2) recorded a distinct rise in Weddell seal Hct during diving and suggested that the total red cell mass is partitioned between general circulation and the splenic reservoir. The concept of splenic red cell storage is well accepted by many researchers, and a diving-induced sympathetic vasoconstriction is thought to be the stimulus for splenic contraction and subsequent injection of oxygenated RBCs into circulation (2,4,6,7). Strong evidence supports this line of reasoning.…”
mentioning
confidence: 96%
“…Dive and postdive catecholamine levels collected from freely diving Weddell and harbor seals show a significant increase over resting levels (6,10,11). In hooded and harp seals, in vitro plethysmographic measurements indicate that ␣-adrenoreceptor activation with epinephrine results in forceful contraction within 1-3 min of administration.…”
mentioning
confidence: 99%
See 3 more Smart Citations